Naujausi Vilniaus senamiesčio aikščių meninio pavidalo pokyčiai: semantinis aspektas - Novickas, Audrius (Journal of Architecture and Urbanism, 2007)
Recent changes of square design in Vilnius old town: semantic aspectDuring the last ten years quite a few city squares in Vilnius went through the renovation process. Refreshed designs and aesthetic qualities of renovated public spaces were discussed rather widely in mass and scientific media. At the same time no considerable attention was paid to the impact of elements in new square compositions on the semantic codes of public spaces. The paper analyses the semantic aspect of changed public squares on the basis of the data collected upon field investigation as well as information from media on the intentions of all sides involved in the renovation process (municipality officials, developers, architects, artists). The main task of the work is to define the messages communicated by new elements in square design and to determine their relation to the rapidly changing sociocultural context of the Lithuanian capital. New square compositions are investigated in the context of the historic development of the same public spaces emphasizing the fact that previous designs were produced in accordance with changing concept of public spaces. A conclusion is made that recent changes in square design in most cases are directed towards conservation rather than transformation of the meaning of the space. New square designs stress upon defensive rather than communicative features of the public space in spite of democratic changes in the Lithuanian society.Article in Lithuanian.Santrauka Semantiniu aspektu nagrinėjami Vilniaus miesto aikščių meninio pavidalo pokyčiai, įvykę per pastarąjį dešimtmetį. Bandoma išsiaiškinti, kokias reikšmių slinktis lėmė viešųjų erdvių renovacija. Atskleidžiami svarbiausių miesto aikščių meninių pavidalų ir jų sociokultūrinio konteksto istorinės raidos charakteringiausi bruožai, išryškinami ankstesnių laikotarpių ir šiandien vykstančių renovacijų skirtumai. Tyrime naudoti duomenys, gauti integruojant lauko tyrimus ir žiniasklaidoje pateiktą informaciją apie kai kurių Vilniaus aikščių naujausių meninių pavidalų ženklinį charakterį. Atskleidžiamos prieštaros tarp šių dienų sociokultūrinio konteksto ir aikščių naujųjų meninių pavidalų semantinio turinio.Reikšminiai žodžiai: miesto aikštė, Vilniaus senamiestis, semantika, meninis pavidalas, transformacija, istorinė raida, sociokultūrinis kontekstas.First published online: 21 May 2013